Edukasi Pemilahan Sampah Sebagai Upaya Menjaga Kebersihan Lingkungan Di SDN Rengasdengklok Selatan 3 - Fahmi Abdu Rafi; Falsha Satria Dwiputra; Sri Septiani; Lydia Maulani; Ferry Adimas Ristansyah; Aldi Dena Kusumah; Wahyudin Wahyudin; Winarno Winarno; Rana Ardila Rahma; Risma Fitriani (KREATIF: Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
To achieve environmental cleanliness, high awareness of cleanliness and health is required. In terms of keeping the environment clean, one very serious problem is a lack of understanding about the waste problem. This problem can be overcome through an educational approach that provides an understanding of various types of waste, both organic and inorganic waste. Efforts to maintain the cleanliness of the surrounding environment must start from an early age. Therefore, this community service activity was carried out to provide education about waste sorting to students at SDN Rengasdengklok Selatan 3 located in Karawang. The purpose of this activity is to increase students' understanding and awareness of the consequences of environmental pollution arising from waste disposal. This activity is carried out with a holistic approach using two main stages, namely socialization and direct practical activities. Through this community service activity, students can not only increase their understanding and awareness of the impacts of waste, but also gain knowledge about the types of waste and the correct way to sort waste.